Fatty infiltration in the musculoskeletal system: pathological mechanisms and clinical implications - Zhu, Yihua; Hu, Yue; Pan, Yalan; Li, Muzhe; Niu, Yuanyuan; Zhang, Tianchi; Sun, Haitao; Zhou, Shijie; Liu, Mengmin; Zhang, Yili; Wu, Chengjie; Ma, Yong; et al. (Frontiers in Endocrinology, 2024)
Fatty infiltration denotes the anomalous accrual of adipocytes in nonadipose tissue, thereby generating toxic substances with the capacity to impede the ordinary physiological functions of various organs. With aging, the musculoskeletal system undergoes pronounced degenerative alterations, prompting heightened scrutiny regarding the contributory role of fatty infiltration in its pathophysiology.Several studies have demonstrated that fatty infiltration affects the normal metabolism of the musculoskeletal system, leading to substantial tissue damage. Nevertheless, a definitive and universally accepted generalization concerning the comprehensive effects of fatty infiltration on the musculoskeletal system remains elusive. As a result, this review summarizes the characteristics of different types of adipose tissue, the pathological mechanisms associated with fatty infiltration in bone, muscle, and the entirety of the musculoskeletal system, examines relevant clinical diseases, and explores potential therapeutic modalities. This review is intended to give researchers a better understanding of fatty infiltration and to contribute new ideas to the prevention and treatment of clinical musculoskeletal diseases.